Development of Product Data Model for Maintenance in Concrete Highway Bridges. (27th August 2013) - Kubota, Satoshi; Mikami, Ichizou
Abstract : The primary objective of this paper is to develop the product data models, in which systematic information is defined for accumulating, exchanging, and sharing in the maintenance of concrete highway bridges. The information requirement and existing issues and solutions were analyzed based on the life cycle and the standardization for sharing. The member data models and business data models that defined design and construction information and accumulated results information were developed. The maintenance business process in which project participants utilize the product data model was described as utilization scenario. The utilization frameworks which define information flow were developed.